PENGARUH TERPAAN INFORMASI BAHAYA MEROKOK PADA BUNGKUS ROKOK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK ROKOK - Gerald Waisaka Ginubahyang S P; Djoko Setyabudi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
This study aims to determine the effect of information on the dangers of smoking on cigarette packets and perceptions of the decision to purchase cigarette products. The population of this study are active smokers, aged 18-40 years, and live in Semarang. The theory used are the Cognitive Response Theory and the Transaction Utility Theory. The sampling technique used non-probability sampling technique with a total sample 100 respondents. Data analysis for the hypothesis used simple linear regression analysis. Data processing uses the Statistical Package for Social Science (SPSS) Version 16.0. The results of the hyphotesis showed that the respondents have high product purchasing decisions. The significance value for the information on the dangers of smoking on cigarette packs variable (X1), and the price perception variable (X2) which is 0,866 and 0,594, which means that there is no influence on the decision to buy cigarette products (Y). So, the researcher suggests to the government that the policy of warning information on the dangers of smoking on cigarette packs and the increase in cigarette excise is deemed ineffective in controlling cigarette purchasing decisions. In the next studies, it is suggested to use other factors that can influence the purchase of cigarette products.